The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1111/cote.12059
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical method for quantitative determination of trace amounts of disperse dye in wastewater

Abstract: The electrochemical behaviour of Disperse Red 13 dye at a glassy carbon electrode was investigated in both organic and aqueous organic mixtures. Best results were obtained in N,N‐dimethylformamide/Britton–Robinson buffer (1:1, v/v), which displays a well‐defined peak at ‐0.40 V (vs Ag/AgCl) owing to reduction of the protonated nitro group. This method can be successfully applied to the electroanalytical determination of Disperse Red 13 in a very simple and inexpensive way. All the differential pulse voltammetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Santos et al [85] has also reported the analysis of the disperse dye Disperse Red 13 (DR13) at glassy carbon electrodes (GCEs) modified with polyglutamic acid (PGA). This dye bears reductive nitro and azo group and presented a well-defined peak at À0.66V when reduced in a mixture of DMF/BR (pH 4, 1:1 v/v) and Bu 4 NBF 4 /DMF.…”
mentioning
confidence: 99%
“…Santos et al [85] has also reported the analysis of the disperse dye Disperse Red 13 (DR13) at glassy carbon electrodes (GCEs) modified with polyglutamic acid (PGA). This dye bears reductive nitro and azo group and presented a well-defined peak at À0.66V when reduced in a mixture of DMF/BR (pH 4, 1:1 v/v) and Bu 4 NBF 4 /DMF.…”
mentioning
confidence: 99%